INNOVATIVE TECHNICAL EDUCATION IN THE AREA OF REDUCING HAZARDOUS SUBSTANCES IN ENVIRONMENTAL TECHNOLOGY - RUZINSKA, Eva (Trends in education, 2012)
The contribution deals with the introduction of up-to-date knowledge gained from research in the field of hazardous substances present in the existing technological processes of technically significant products from the perspective of operational and environmental safety. At the same time, it is the attention paid to the issue of transfer of systematic measures for the reduction of hazardous substances in the field of technical and environmental education for the target group of students in the two stages of higher education study programmes Environmental technology and also the Protection of persons and property against fire. Assuming the effective use of knowledge for professionals in the field of lifelong security and environmental education.
Keywords: hazardous substances; innovative technical education; environmental technology.